Irreversible Investments and Volatile Markets: A Study of the Chemical Processing Industry - Bell, Gregory K.; Campa, José M. (The Review of Economics and Statistics, 1997)
This paper investigates the empirical effect of volatility on irreversible investments. We use a sample of chemical products in the United States and the European Union to test the impact of volatility on new investments in capacity. We distinguish among three sources of volatility: exchange rates, input prices, and product demand. We find that the effects of volatility on the amount of capacity investment differ depending on the source of volatility. Input prices and product demand volatility do not appear to have a material and statistically significant effect in either the United States or the European Union. In contrast, exchange rate volatility has a significant negative impact on investment by chemical manufacturers in the European Union.